Respuesta :

Answer:

4, 8) and  (-2, -4)

Step-by-step explanation:

y = x² - 8    and y = 2x .

Substitute  y = 2x into the first equation.

2x = x² - 8  

0 = x² - 2x - 8       Add -2x to both sides.

0 =  ( x - 4)(x + 2)       Factor

0 = x - 4  ;   0 = x + 2

  x = 4   ; x = - 2

Solve y = 2x  when x = 4                   solve y = 2x when x = -2

          y = 2(4)                                              y = 2(-2)

          y = 8                                                   y =  -4

    (4, 8) and  (-2, -4)

ACCESS MORE